2001
DOI: 10.1080/00480169.2001.36211
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to macrocyclic lactone anthelmintics byHaemonchus contortusandOstertagia circumcinctain sheep in New Zealand

Abstract: As well as providing further evidence that it can no longer be automatically assumed that macrocylic lactone anthelmintics will be effective on sheep farms in this country, these findings also present a warning that increasingly complex parasite control options may have to be faced in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 25 publications
4
14
0
Order By: Relevance
“…As can be seen in Table 2, this anthelmintic showed the highest effectiveness rate (stand-alone) in five studies involving sheep (CUNHA et al, 1998;THOMAZ-SOCCOL et al, 2004;CEZAR et al, 2010;LIMA et al, 2010b;SCZESNY-MORAES et al, 2010) and in three studies involving goats (AHID et al, 2007; RODRIGUES et al, 2007; LIMA et al, 2010b). Although its mechanism of action is similar to that of ivermectin, several authors around the world have observed the greater effectiveness of moxidectin in strains resistant to ivermectin (BARNES et al, 2001;VICKERS et al, 2001;LLOBERAS et al, 2013). Prichard et al (2012) ascribed the difference in the effectiveness of these two antiparasitics to different interactions in glutamate-gated ion channels where they act, and to different levels of expression of ABC proteins.…”
Section: Developments In Research and The Effectiveness Of Anthelmintmentioning
confidence: 99%
“…As can be seen in Table 2, this anthelmintic showed the highest effectiveness rate (stand-alone) in five studies involving sheep (CUNHA et al, 1998;THOMAZ-SOCCOL et al, 2004;CEZAR et al, 2010;LIMA et al, 2010b;SCZESNY-MORAES et al, 2010) and in three studies involving goats (AHID et al, 2007; RODRIGUES et al, 2007; LIMA et al, 2010b). Although its mechanism of action is similar to that of ivermectin, several authors around the world have observed the greater effectiveness of moxidectin in strains resistant to ivermectin (BARNES et al, 2001;VICKERS et al, 2001;LLOBERAS et al, 2013). Prichard et al (2012) ascribed the difference in the effectiveness of these two antiparasitics to different interactions in glutamate-gated ion channels where they act, and to different levels of expression of ABC proteins.…”
Section: Developments In Research and The Effectiveness Of Anthelmintmentioning
confidence: 99%
“…In New Zealand, parasitism has traditionally been controlled using anthelmintics, but anthelmintic resistance in endoparasites of sheep has become increasingly common (Vickers et al 2001). In addition, there is increasing consumer concern regarding chemical residues in meat and the effect of anthelmintics on the environment (Wall & Strong 1987).…”
Section: Introductionmentioning
confidence: 99%
“…In 2000, the fi rst cases of resistance to the ML class of compounds were reported from sheep fl ocks in New Zealand (Leathwick et al 2000;Mason et al 2001;Hughes and McKenna 2005); populations of Ostertagia circumcincta showed resistance to ivermectin. Soon after, ML resistance in both O. circumcincta and H. contortus on the same farm was reported (Vickers et al 2001).…”
Section: Introductionmentioning
confidence: 91%